2021
DOI: 10.35249/rche.47.3.21.09
|View full text |Cite
|
Sign up to set email alerts
|

On the distribution of Vagrans egista (Cramer, 1780) in West Bengal, India

Abstract: Vagrans egista (Cramer, 1780) is reported for the first time from southern part of West Bengal, India. The Raygar forest of Bankura district in the plateau region is the second locality for the reported species in West Bengal, which extends the distribution range (aerial distance: 525 km) of the species from its known locality, Buxa Tiger Reserve of Alipurduar district in the state. This paper also reports occurrence of Rapala pheretima and Gerosis bhagava in Bankura district for the first time. Importance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…They found 117 species of butterflies. This region is largely unexplored (Mirza and Mondal 2018;Mondal et al, 2020), but some interesting butterfly species distributions (Roy et al, 2021) and a new host plant of Papilio crino (Fabricius) has been reported by Mukherjee and Ghosh (2018). The objective of this present study is to understand the availability of the larval host plants in the Bankura district.…”
Section: Introductionmentioning
confidence: 99%
“…They found 117 species of butterflies. This region is largely unexplored (Mirza and Mondal 2018;Mondal et al, 2020), but some interesting butterfly species distributions (Roy et al, 2021) and a new host plant of Papilio crino (Fabricius) has been reported by Mukherjee and Ghosh (2018). The objective of this present study is to understand the availability of the larval host plants in the Bankura district.…”
Section: Introductionmentioning
confidence: 99%